2015
DOI: 10.1016/j.ijvsm.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of macrolides containing marine actinomycetes formulation versus ciprofloxacin ophthalmic solution in controlling Pseudomonas aeruginosa induced conjunctivitis on rabbit model

Abstract: P. aeruginosa. Compared to ciprofloxacin ophthalmic solution our RAM24C2 extract formulation hastens the cure of conjunctivitis developed rabbits and need less dosage frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In the present study, resistance of P. aeruginosa strains to Kanamycin, and Tetracycline were 91.8%, and 94.5%, respectively, similar to results of Wahaab et al 21 study, who recorded resistance to those antibiotics were 100%. Resistance of P. aeruginosa strains to Aztreonam, Meropenem, Cefepime, Piperacillin/Tazobactam, Gentamicin, and Imipenem were 75.6%, 73%, 94.5%, 72.9%, 81%, and 78.3%, respectively, similar to results of Shokri et al 7 study, who recorded resistance to those antibiotics were 64.5%, 85.4%, 85.4%, 74%, 79.2%, and 84.4%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, resistance of P. aeruginosa strains to Kanamycin, and Tetracycline were 91.8%, and 94.5%, respectively, similar to results of Wahaab et al 21 study, who recorded resistance to those antibiotics were 100%. Resistance of P. aeruginosa strains to Aztreonam, Meropenem, Cefepime, Piperacillin/Tazobactam, Gentamicin, and Imipenem were 75.6%, 73%, 94.5%, 72.9%, 81%, and 78.3%, respectively, similar to results of Shokri et al 7 study, who recorded resistance to those antibiotics were 64.5%, 85.4%, 85.4%, 74%, 79.2%, and 84.4%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…To concentrate the antimicrobial metabolite produced by the actinomycetes, medium were extracted using hexane (HEX), dichloromethane (DCM) and ethyl acetate (AcOEt) (1000 mL), in increasing order of polarity. Then, the organic phase, containing the active metabolite, was separated from the aqueous phase with a separatory funnel and the extracts were concentrated in a rotary evaporator at 37 °C [17]. Crude extracts obtained from the isolates were dissolved in DMSO and used as a stock solution to determine antimicrobial activity to the test pathogens, using DMSO as a control treatment.…”
Section: Secondary Screening and Molecular Identification Of Actinomy...mentioning
confidence: 99%
“…[5] Wahaab et al, 2015, have isolated marine actinomycetes from Rameswaram and have identified the strain RAM24C2 with the highest antibacterial activity against ocular pathogen Pseudomonas aeruginosa. [6] Rameswaram is one of the major hotspots for exploration of novel actinomycetes species and extraction of bioactive secondary metabolites.…”
Section: Original Articlementioning
confidence: 99%